A type of ethylaminethiourea passivated perovskite film and preparation method thereof and perovskite solar cell

By using ethylamine thiourea as a passivating agent in perovskite solar cells to form a passivation layer, the efficiency and stability problems caused by defects in perovskite films are solved, and the photoelectric conversion efficiency is improved.

CN117202749BActive Publication Date: 2025-05-02DALIAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311164991.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-05-02
Estimated Expiration
2043-09-08

AI Technical Summary

Technical Problem

There are defects in perovskite solar cells that affect their photovoltaic parameters, resulting in non-radiative recombination of carriers, thereby reducing cell efficiency and stability.

Method used

Ethionine thiourea (AET) is used as the passivation agent to form a passivation layer with the surface of the perovskite film to reduce defects and ion migration channels and improve the quality of perovskite materials.

Benefits of technology

The photoelectric conversion efficiency and stability of perovskite solar cells have been significantly improved, and the photoelectric conversion efficiency has been increased from 18.19% to 20.21%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117202749B_ABST
    Figure CN117202749B_ABST
Patent Text Reader

Abstract

The present invention discloses a class of ethylenethiourea-passivated perovskite thin films, a preparation method thereof, and a perovskite solar cell. The perovskite thin film comprises a perovskite thin film and a passivation layer, the passivation layer is located on the surface of the perovskite thin film, and the passivation molecules of the passivation layer have a chemical formula of C3H9N3S·2HBr. The passivation molecule ethylenethiourea (AET) of the present invention has three amino groups and one S-donor. Among them, the amino group can form a hydrogen bond with the iodine atom in the perovskite crystal, and the S-donor can form a Lewis acid-base adduct with the Pb atom or form a hydrogen bond with NH. At the same time, due to the efficient passivation of defects by ethylenethiourea as a passivating agent, the channels for ion migration are reduced, so that the ion migration phenomenon in the perovskite material with ionic crystal properties is significantly inhibited, effectively improving the photoelectric conversion efficiency and stability of the device. The photoelectric conversion efficiency (PCE) is increased from 18.19% to 20.21%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of interface engineering passivation of perovskite solar cells, and in particular relates to a perovskite film passivated with ethylaminethiourea and a preparation method thereof, and a perovskite solar cell. Background Art

[0002] The development and utilization of fossil energy has greatly promoted the development of productivity and social progress, but it has also inevitably brought about environmental pollution and global warming, affecting people's health. From the perspective of sustainable development, fossil energy, as a non-renewable energy, is becoming increasingly exhausted. As one of the most promising renewable energy sources, solar energy is clean, pollution-free and has huge energy. It is known as one of the most promising new energy sources to replace fossil energy, and therefore has attracted the attention of scientists from all over the world. The technology for utilizing solar energy has also been fully developed in recent years, and various devices that utilize solar energy have "bloomed in bloom". Making full use of solar energy can reduce CO2 emissions and reduce dependence on fossil energy.

[0003] A solar cell is a battery that converts solar energy into electrical energy through the photoelectric effect or photochemical reaction. From the first generation of single-crystal silicon and polycrystalline silicon solar cells, to the second generation of amorphous silicon and polycrystalline silicon thin-film cells, to new concept cells such as dye-sensitized and perovskite solar cells, solar cells that use solar energy to generate electricity have ushered in a new era. Among them, perovskite solar cells, as one of the most promising third-generation solar cells, have the advantages of high light absorption coefficient, long carrier diffusion length, wide light absorption range, and adjustable band gap. Since its inception, it has been a hot research topic in the scientific research community. Perovskite solar cells have developed very rapidly. When they were first discovered, their efficiency was only 3.81%. In just over a decade, the efficiency has risen rapidly to 25.7%.

[0004] Defects in perovskite films can affect the photovoltaic parameters of the cell, such as the open circuit voltage (V OC ), short-circuit current density (J SC ), fill factor (FF), and PCE. There are four main types of defects in organic-inorganic hybrid perovskite films: (1) intrinsic defects. (2) impurities, such as Li from Spiro-OMeTAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene) + , and many defects from other raw materials. (3) Two-dimensional defects, including grain boundaries and surface defects. (4) Three-dimensional defects, such as lead clusters. These defects can cause non-radiative recombination of carriers, which in turn affects the photovoltaic parameters of solar cells. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, optimize the performance of perovskite photovoltaic cells, and use ethylaminethiourea (AET for short) as a passivator for defect passivation of perovskite films.

[0006] In order to achieve the above object, the technical solution of the present invention is as follows:

[0007] On one hand, the present invention provides a type of ethaminethiourea passivated perovskite film, comprising a perovskite film and a passivation layer, wherein the passivation layer is located on the surface of the perovskite film, and the passivation molecule chemical formula of the passivation layer is C3H9N3S·2HBr.

[0008] In the above technical solution, further, the chemical composition of the perovskite film is FA 0.88 Cs 0.12 PbI3.

[0009] Another aspect of the present invention provides a method for preparing the above-mentioned ethaminethiourea passivated perovskite film, the method comprising the following steps:

[0010] (1) dissolving the passivation molecule in a solvent to obtain a passivation molecule solution;

[0011] (2) spin coating the passivation molecule solution onto the surface of the perovskite film, annealing to form a passivation layer, and obtaining the perovskite film;

[0012] The chemical formula of the passivation molecule is C3H9N3S·2HBr.

[0013] In the above technical solution, further, the solvent is isopropanol or ethanol.

[0014] In the above technical solution, further, the concentration of the passivation molecule solution is 0.05-2.0 mg / ml.

[0015] In the above technical solution, further, the spin coating parameters are: the spin coating speed is 3000 rpm / s, and the spin coating time is 30s.

[0016] In the above technical solution, further, the annealing temperature is 60° C. and the annealing time is 20 min.

[0017] The present invention also provides an application of the above-mentioned ethylaminethiocarbamide passivated perovskite film in a perovskite solar cell for preparing a perovskite solar cell device. The cell is a nip structure, and the cell comprises, from bottom to top, a conductive layer, an electron transport layer, a perovskite active layer, a hole transport layer and a metal electrode layer; the perovskite active layer is the above-mentioned ethylaminethiocarbamide passivated perovskite film.

[0018] In the above technical solution, further, the conductive substrate is glass.

[0019] In the above technical solution, further, the electron transport layer material is a titanium dioxide (TiO2) film or a tin dioxide (SnO2) film.

[0020] In the above technical solution, further, the hole transport layer material is Spiro-OMeTAD doped with 4-tert-butylpyridine (T-BP), lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) and FK209 Co(III)TFSI.

[0021] In the above technical solution, further, the metal electrode layer material is Ag or Au, and the thickness is 60-90nm.

[0022] The beneficial effects of the present invention are:

[0023] The passivation molecule ethylaminethiourea (AET) of the present invention has three amino groups and one S-donor, wherein the amino groups can form hydrogen bonds with iodine atoms in the perovskite crystal, and the S-donor can form Lewis acid-base adducts with Pb atoms or form hydrogen bonds with NH. At the same time, since ethylaminethiourea is used as a passivator to efficiently passivate defects, the channels for ion migration are reduced, so that the ion migration phenomenon in the perovskite material with ionic crystal properties is significantly suppressed, and the photoelectric conversion efficiency and stability of the device are effectively improved, and the photoelectric conversion efficiency (PCE) is increased from 18.19% to 20.21%. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The device structure of the perovskite solar cell of the present invention;

[0025] Figure 2 The ultraviolet absorption spectra of the perovskite films of Example 1 and Comparative Example 1;

[0026] Figure 3 Steady-state fluorescence spectra of the perovskite films of Example 1 and Comparative Example 1;

[0027] Figure 4 X-ray diffraction patterns of the perovskite films of Example 1 and Comparative Example 1;

[0028] Figure 5 The scanning electron microscope images of the perovskite films of Example 1 and Comparative Example 1, a is Comparative Example 1, and b is Example 1;

[0029] Figure 6 The water contact angle test diagrams of the perovskite films of Example 1 and Comparative Example 1, a is Comparative Example 1, and b is Example 1;

[0030] Figure 71 is a JV curve diagram of the device of Example 1 and Comparative Example 1 measured based on the SCLC model under dark conditions in the present invention, a is Comparative Example 1, and b is Example 1;

[0031] Figure 8 Fourier infrared test images of the perovskite films of Example 1 and Comparative Example 1;

[0032] Fig. 9 The XPS spectra of the perovskite films of Example 1 and Comparative Example 1, a represents the Pb element, b represents the N element, c represents the I element, and d represents the S element;

[0033] Fig.10 JV curves of the devices of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with specific embodiments and comparative examples so that those skilled in the art can better understand the present invention. However, the examples described here are only used to explain the present invention, and the present invention is not limited thereto.

[0035] The experimental drugs used in the following examples were all analytically pure reagents and could be used directly unless otherwise specified.

[0036] Example 1

[0037] The process of making perovskite solar cell devices is as follows:

[0038] (1) Processing method of FTO conductive glass:

[0039] Wipe the conductive glass with a dust-free cloth dipped in a detergent aqueous solution to preliminarily remove impurities on the glass surface, then ultrasonically clean it with a detergent aqueous solution, deionized water (twice), acetone, and isopropanol for 20 minutes respectively, and blow dry it with a nitrogen spray gun for later use;

[0040] (2) Preparation method of electron transport layer:

[0041] The cleaned conductive glass was first treated with an ozone plasma cleaner before use to remove organic impurities on the surface and increase hydrophilicity. Then, a 15% SnO2 aqueous solution was diluted in a ratio of SnO2 solution: deionized water (containing 3.75 mg / ml KCl) = 1:4 (v / v), and then filtered with a 0.22 μm polyethersulfone filter. The prepared tin oxide solution was spin-coated on a conductive glass substrate at a speed of 4000 rpm / s for 30 seconds, and then annealed at 150°C for 30 minutes.

[0042] (3) Preparation method of perovskite active layer:

[0043] 0.1 mg of AET solid powder was dissolved in 1 ml of isopropanol and placed in ultrasound to fully dissolve. As the concentration increased, the color gradually deepened. After dissolution, it was placed aside for use. A precursor solution of perovskite composition of PbI2 (1.05 M), FAI (0.88 M), CsI (0.12 M) and chloromethylamine MACl (0.18 M) was prepared in a vacuum glove box. The solvent was a mixed solution of dimethyl sulfoxide and N,N-dimethylformamide (1:8, v / v). The prepared precursor solution was stirred for more than 4 hours. The perovskite precursor solution was filtered with a 0.22 μm polytetrafluoroethylene filter membrane before spin coating. Before preparing the perovskite film, the glass substrate was first placed in a plasma cleaner for at least 3 m. in, so as to enhance the hydrophilicity of the substrate. The perovskite film was prepared by a one-step method. The substrate was placed on a spin coater, 50 μl of the precursor solution was dripped, and the substrate was first spin-coated at 1000 rpm / s for 9 seconds, and then spin-coated at 5000 rpm / s for 30 seconds. 150 μl of the anti-solvent chlorobenzene was dripped at 5000 rpm / s for 16 seconds. After the spin coating, annealing was performed at 100°C for 30 minutes. Subsequently, the AET solution dissolved in isopropanol was filtered with a 0.22 μm polytetrafluoroethylene filter membrane, and 50 μl of AET solution was spin-coated at 3000 rpm / s for 30 seconds. After the spin coating, annealing was performed at 60°C for 20 minutes. After natural cooling, a black mirror AET passivation layer was formed.

[0044] (4) Preparation method of hole transport layer:

[0045] A hole transport layer precursor solution was prepared in a vacuum glove box. The hole transport layer solution was prepared by dissolving a mixture of SpiroOMeTAD (72.3 mg), T-BP (28.8 μl) and Li-TFSI (17.5 μl) (520 mg Li-TFSI / 1 mL acetonitrile) in 1 mL chlorobenzene, stirring for more than 2 h, and filtering with a 0.22 μm polytetrafluoroethylene filter before use. 50 μL of the hole transport layer precursor solution was dropped on the surface of the substrate coated with the perovskite film, and spin-coated at 3000 rpm / s for 30 s. After the spin-coating, the solution was annealed at 50°C for 5 min.

[0046] (5) Preparation method of counter electrode:

[0047] After the hole transport layer was spin-coated, a scraper was used to etch the opposite side to scrape out a blank area of ​​3×15 mm, exposing the FTO layer as the negative electrode of the battery. The processed film was neatly placed on the customized mask plate, and the evaporation rate was adjusted to 0.02 nm / s under vacuum conditions (1×10 -4 Pa) Use a vacuum coating machine to evaporate a layer of 80nm thick gold or silver electrode.

[0048] Comparative Example 1

[0049] The structure of FTO / SnO2 / FA was prepared. 0.88 Cs 0.12 The preparation method of the PbI3 / Spiro-OMeTAD / Ag device is the same as that of Example 1, except that the perovskite active layer does not contain an AET passivation layer, and the remaining steps are the same.

[0050] Table 1 is the test data of the perovskite solar cell devices of Example 1 and Comparative Example 1.

[0051] Table 1 Comparison of performance parameters of solar cells in comparative example 1 and embodiment 1

[0052]

[0053] The perovskite films described in Example 1 and Comparative Example 1 were subjected to UV-visible light absorption tests. The test spectra are shown in FIG. Figure 2 It can be seen that the diffraction peak position of the perovskite film passivated with 0.1 mg / ml AET is basically consistent with the diffraction peak position without addition.

[0054] The perovskite films described in Example 1 and Comparative Example 1 were subjected to steady-state fluorescence testing. The test spectra are shown in FIG. Figure 3 As shown in Figure 2, the PL intensity increased significantly after AET passivation, indicating that the non-radiative recombination process caused by defects was reduced and the quality of the perovskite film was significantly improved.

[0055] The perovskite films described in Example 1 and Comparative Example 1 were subjected to X-ray diffraction tests, and the test spectra were as follows: Figure 4 As shown in the figure. The perovskite characteristic peak intensity of the perovskite film passivated by AET is significantly enhanced, and the characteristic peak intensity of lead iodide is significantly reduced. It can be seen that AET passivates the unbonded lead ions in the lattice, reduces their recombination with photogenerated carriers, and improves the quality of the perovskite film.

[0056] The perovskite films described in Example 1 and Comparative Example 1 were tested using a scanning electron microscope. The test spectra are shown in FIG. Figure 5 As shown. It can be seen that the surface of the perovskite film passivated by AET is denser, the grains are larger, and there are fewer grain boundaries, which helps the perovskite layer to have good contact with the hole layer, promotes hole transport, blocks electrons from entering the hole layer, reduces non-radiative recombination, and helps improve device efficiency.

[0057] The water contact angle of the perovskite film described in Example 1 and Comparative Example 1 was tested. The test results are as follows: Figure 6 As shown in Figure 2, the water contact angle increases from 55.5° to 75.5°, which shows that the hydrophobicity of the AET-passivated perovskite film increases, thus significantly improving the humidity stability of the perovskite film.

[0058] The JV curves of the devices before and after passivation of the perovskite films described in Example 1 and Comparative Example 1 were measured based on the SCLC model under dark conditions. The test results are as follows: Figure 7 As shown. According to the formula Nt = 2εε0V TFL / eL 2 The defect state density of the device before and after passivation is calculated, where L is the film thickness, ε r is the relative dielectric constant, ε0 is the vacuum dielectric constant, V TFL The smaller the value, the smaller the defect state density. After AET passivation, V TFL This further illustrates the reduction of defects after passivation.

[0059] The perovskite films described in Example 1 and Comparative Example 1 were tested for Fourier infrared spectra. The test results are as follows: Figure 8 As shown. It can be observed that the NH characteristic peak of AET is at 1627cm -1 When reacted with a certain amount of lead iodide, the NH characteristic peak of the AET system shifted to 1615 cm -1 ), the CN characteristic peak and the CS characteristic peak are shifted to varying degrees, which confirms the interaction between AET and PbI2. This indicates that the S in AET and the Pb in the perovskite interact to form a Lewis acid-base pair, which plays a role in stabilizing the crystal structure of PbI2.

[0060] The XPS spectra of the perovskite films described in Example 1 and Comparative Example 1 were tested. The test results are as follows: Fig. 9 As shown. Fig. 9 a It can be observed that Pb in the perovskite film passivated by AET 4f The binding energy shifts, Fig. 9 b It can be seen that the N 1s The binding energy also shifts. Fig. 9 As can be seen from c, I 3d The binding energy also changes to varying degrees. The changes in the binding energy of Pb and I elements support the changes in the FTIR spectrum, indicating that AET can bind to Pb 2+ ,I - Coordination occurs. Fig. 9 d It can be seen that S appears at 164.5eV and 165.9eV 2p The broad peak indicates the interaction between S and Pb atoms.

[0061] The perovskite solar cell device was prepared according to the method of Example 1, and the JV test was carried out under AM 1.5G simulated sunlight. The results are as follows: Fig.10 As shown, it can be seen that the photovoltaic performance of the device after passivation is improved, and the photoelectric conversion efficiency is increased from 18.19% to 20.21%.

[0062] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a perovskite film passivated with ethylaminethiourea, characterized in that: The invention comprises a perovskite film and a passivation layer, wherein the passivation layer is located on the surface of the perovskite film, the passivation molecule chemical formula of the passivation layer is C3H9N3S·2HBr, and the chemical composition of the perovskite film is FA 0.88 Cs 0.12 PbI3; The method comprises the following steps: (1) dissolving the passivation molecule in a solvent to obtain a passivation molecule solution; (2) Spin-coating the passivation molecule solution onto the surface of the perovskite film, annealing, forming a passivation layer, and obtaining the perovskite film.

2. The preparation method according to claim 1, characterized in that: The solvent is isopropanol or ethanol.

3. The preparation method according to claim 1, characterized in that: The concentration of the passivation molecule solution is 0.05-2.0 mg / ml.

4. The preparation method according to claim 1, characterized in that: The spin coating parameters are: spin coating speed is 3000 rpm / s, and spin coating time is 30 s.

5. The preparation method according to claim 1, characterized in that: The annealing temperature is 60° C. and the annealing time is 20 min.

6. A method for passivating a perovskite film passivated with ethaminethiourea prepared by the preparation method according to any one of claims 1 to 5 in a perovskite solar cell, characterized in that: Used to prepare a perovskite solar cell device, the cell is a nip structure, and the cell comprises from bottom to top: a conductive layer, an electron transport layer, a perovskite active layer, a hole transport layer and a metal electrode layer; the perovskite active layer is a perovskite film passivated with ethaminethiourea obtained by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of blue light film, blue light film and luminescent device

    CN116249417A